In Silico Analyses of Burial Codon Bias Among the Species of Dipterocarpaceae Through Molecular and Phylogenetic Data. (March 2019) - Biswas, Raju; Panja, Anindya Sundar; Bandopadhyay, Rajib
Introduction: DNA barcode, a molecular marker, is used to distinguish among the closely related species, and it can be applied across a broad range of taxa to understand ecology and evolution. MaturaseK gene ( matK ) and rubisco bisphosphate carboxylase/oxygenase form I gene ( rbcL ) of the chloroplast are highly conserved in a plant system, which are used as core barcode. This present endeavor entails the comprehensive examination of the under threat plant species based on success of discrimination on DNA barcode under selection pressure. Result: The family Dipterocarpaceae comprising of 15 genera is under threat due to some factors, namely, deforestation, habitat alteration, poor seed, pollen dispersal, etc. Species of this family was grouped into 6 clusters for matK and 5 clusters and 2 sub-clusters for rbcL in the phylogenetic tree by using neighbor-joining method. Cluster I to cluster VI of matK and cluster I to cluster V of rbcL genes were analyzed by various codon and substitution bias tools. Mutational pressure guided the codon bias which was favored by the avoidance of higher GC content and significant negative correlation between GC12 and GC3 (in sub-cluster I of cluster I [0.03 < P ], cluster I [0.00001 < P ], and cluster II [0.01 < P ] of rbcL, and cluster IV [0.013 < P ] of matK ). After refining the results, it could be speculated that the lower null expectation values ( R = 0.5 or <0.5) were less divergent from the evolutionary perspective. Apart from that, the higher null expectation values ( R = >0.85) also showed the same result, which possibly could be due to the negative impact of very high and low transition rate than transversion. Conclusion: Through the analysis of inter-generic, inter/intra-specific variation and phylogenetic data, it was found that both selection and mutation played an important role in synonymous codon choice in these genes, but they acted inconsistently on the genes, both matK and rbcL . In vitro stable proteins of both matK and rbcL were selected through natural selection rather than mutational selection. matK gene had higher individual discrimination and barcode success compared with rbcL . These discriminatory approaches may describe the problem related to the extinction of plant species. Hence, it becomes very imperative to identify and detect the under threat plant species in advance.